Rapid Observational Assessment on Urban Forest Trails Established at UMS Peak of Universiti Malaysia Sabah - Shen, Lim Wing; Binti Anuar, Syazwani Nisa; Mojiol, Andy R (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2019)
Universiti Malaysia Sabah housed a dense secondary forest that served as one of the urban forests and green lungs in Kota Kinabalu of Sabah, and this urban forest was known as UMS Peak. Few formal and informal trails were established within UMS Peak, and their conditions were yet to be properly evaluated since their establishments in 2009. Therefore, a preliminary assessment was required to assess existing conditions of these urban forest trails within UMS Peak. Two identified formal trails (Waterfall Trail and Chancellery Trail) and one informal trail (Kg. E Trail) were selected for rapid visualobservation assessment. Distance from starting point, elevation, slope steepness, trail forest structure condition, visual value, and management condition for each trail were assessed at the sample posts established every 100 m along the trail. Surrounding plant community, facility and infrastructure, slope steepness, elevation, attractive scenicfeatures, recreational impact, and ground cover were insignificant different, while trail visibility, trail width, soil compaction, forest layer, potential risk, surrounding scenic invisibility, and trail management condition were determined to be significantly different, between the three trails. Chancellery Trail suffered from worse recreational impact, andthen Waterfall Trail was determined to be worse in trail condition compared to Kg. E Trail. Additionally, interior segments were discovered as main contributors to significant differences between trails. Therefore, further detailed evaluation on these informal and formal trails are required to obtain accurate information and much comprehensive understanding on factors with significant influences towards overall and segment conditions of these three different trails.